2016
DOI: 10.1002/ece3.2503
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic congruence between subtropical trees and their associated fungi

Abstract: Recent studies have detected phylogenetic signals in pathogen–host networks for both soil‐borne and leaf‐infecting fungi, suggesting that pathogenic fungi may track or coevolve with their preferred hosts. However, a phylogenetically concordant relationship between multiple hosts and multiple fungi in has rarely been investigated. Using next‐generation high‐throughput DNA sequencing techniques, we analyzed fungal taxa associated with diseased leaves, rotten seeds, and infected seedlings of subtropical trees. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
1
13
1
Order By: Relevance
“…Although the influence of plant phylogeny on soil fungal communities was not as strong in our study as that reported in some studies for biotrophic fungal groups [18,21,22] and in analyses at local scales [31], the significant effect of plant phylogeny on soil fungal community composition is nonetheless of great ecological and evolutionary importance. The finding reflects the pronounced role of trees as superorganisms in the forest ecosystem and highlights that the evolutionary association between woody plants and fungi may be broadened to both saprophytic and biotrophic groups in the neighboring soil around trees [31,80], even at a broad spatial scale.…”
Section: Effects Of Plant Phylogeny and Species Identity On Communitycontrasting
confidence: 71%
See 1 more Smart Citation
“…Although the influence of plant phylogeny on soil fungal communities was not as strong in our study as that reported in some studies for biotrophic fungal groups [18,21,22] and in analyses at local scales [31], the significant effect of plant phylogeny on soil fungal community composition is nonetheless of great ecological and evolutionary importance. The finding reflects the pronounced role of trees as superorganisms in the forest ecosystem and highlights that the evolutionary association between woody plants and fungi may be broadened to both saprophytic and biotrophic groups in the neighboring soil around trees [31,80], even at a broad spatial scale.…”
Section: Effects Of Plant Phylogeny and Species Identity On Communitycontrasting
confidence: 71%
“…Gilbert and Webb [17] found that the likelihood that a pathogenic fungus successfully infected two tree species decreased with increasing plant phylogenetic distance in a tropical forest. Liu et al [18] observed a phylogenetically congruent pattern between woody plants and foliar/soil-borne pathogenic fungi; that is, congeneric host trees were usually infected by the same or closely related fungi. Likewise, strong plant phylogenetic signal was also detected in symbioses involving woody plants, arbuscular mycorrhizal (AM), and ectomycorrhizal (EcM) fungi [19][20][21][22], with closely related woody plants interacting with closely related fungal partners.…”
Section: Introductionmentioning
confidence: 99%
“…This included differences in the repertoire of secreted effector proteins and activity of pathogenicity-related genes. In apparent contrast, ecologists predict pathogen-host compatibility based on overall plant phylogeny (Gilbert and Webb 2007;Liu et al 2015bLiu et al , 2016: more related plants are more likely to be host to the same pathogen (Gilbert and Webb 2007). For instance, Parker et al (2015) derived a model, based on over 200 known host -fungal pathogen associations, that predicts the probability for two plant species to share the same particular pathogen based on the phylogenetic distance.…”
Section: Indirect Neighbour Effects Via the Root Microbiomementioning
confidence: 99%
“…Researchers have specifically applied these concepts to plant–herbivore relationships and to plant–pathogen relationships, and these studies have shown that evolutionary history is important for both kinds of enemies . Some studies have examined the Janzen–Connell hypothesis in a phylogenetic context by analyzing communities of plants and associated fungi, and these studies suggest that coevolution may promote diversity in both groups . There has also been a growing awareness of the importance of plant defensive chemicals to potential pathogens as well as to potential herbivores .…”
Section: Discussionmentioning
confidence: 99%
“…114 Some studies have examined the Janzen-Connell hypothesis in a phylogenetic context by analyzing communities of plants and associated fungi, and these studies suggest that coevolution may promote diversity in both groups. 119 There has also been a growing awareness of the importance of plant defensive chemicals to potential pathogens as well as to potential herbivores. 120,121 A recent review of plant-pathogen interactions hypothesized that coevolution between plants and pathogens may promote enemy specialization and host diversification, as proposed by Ehrlich and Raven for plants and herbivores.…”
Section: Discussionmentioning
confidence: 99%